Utilization of Microwave Pretreatment Process Degradation of Lignin in Pulp Sugarcane (Bagasse) in Bioethanol Production - Argo, Bambang Dwi; Hendrawan, Yusuf; Widyawati, Niken Lila (Jurnal Teknologi Pertanian, 2014)
Bagasse contains lignocellulose can be broken down into glucose as bioethanol production. In this research, bagasse pretreatment was conducted using NaOH solution and utilizing microwave irradiation in a microwave. The purpose of this research was to determine the effect of long exposure to microwave with NaOH concentration on the cellulose content. Pretreatment of bagasse is done in the microwave with the variation of time (10 minutes, 20 minutes, 30 minutes, and 40 minutes) and the variation of the concentration of NaOH (1 molar, 2 molar, and 3 molar). Characteristics before and after treatment were analyzed by Scanning Electron Microscopy (SEM). The results showed that the highest content of cellulose with an average of 86.85% by treatment with NaOH 3 molar and long exposure to microwave 40 minutes. While the lignin content decreased from 17.56% to 5.47% and a hemicellulose content of 20.98% to 2.58%.Keywords: lignocellulose, NaOH, SEMÂ